Kompleksnaja ocenka sorevnovatel'noj dejatel'nosti i techniceskoj podgotovlennosti mnogoborcev v bar'ernom bege s ispol'zovaniem videoanaliza - Ogandzhanov, A. L. (Vestnik sportivnoj nauki; Sports science bulletin, 2020)
Athletics decathlon includes seven technical types. Technical skills largely determine the result of the whole decathlon. The research is devoted to the development of a method for a comprehensive assessment of competitive activity and technical readiness of decathletes in hurdles - one of the most technically complex types of the competition. The methods included a video analysis of competitive activity and technical readiness of qualified decathletes in overcoming the barrier in technical training. Control includes the timing of passing the starting period, barrier sections and finish line of the distance, the speed characteristic of the race, all the techniques of overcoming the barrier, the implementation of high-speed potential of an athlete on the hurdling. The dynamics of speed at the barrier distance is estimated according to the index, which indirectly characterizes various types of special training of the athletes: the technical side and speed-strength training as well as speed endurance. This creates opportunities for more effective management of special training of male athletes at the stages of sports improvement and high skills.